Hubungan Strategi Umpan Balik (Feedback), Motivasi Berprestasi dan Hasil Belajar Dalam Pembelajaran PPKn di SMK - Sastro Slamet, Sumarno (Universitas Nusantara PGRI Kediri, 2020)
Gagne (1985) and Marzano (2004), state that one of the important activities in effective learning is giving feedback on the results of evaluations or assignments that students work on. This study aims to examine the effect of providing feedback on learning outcomes (understanding and application of concepts) to students who have different achievement motivations in learning Pancasila and Citizenship Education in SMK. This study uses a quasi-experimental research design (Quasi Experiment). The subjects of this study were 126 students of SMK Negeri 5 Malang. The research instrument used to collect data was an achievement motivation questionnaire and a test of understanding and applying concepts. The research data were analyzed using the MANOVA (Multivariate Analysis of Variance) method with 2x2 factorial. The research findings are: (1) there are differences in learning outcomes (understanding and application of concepts) between groups of students who are given direct (immediate) and indirect (delayed) feedback treatment; (2) there are differences in learning outcomes (understanding and application of concepts) between groups of students who are low and high achievers and (3) the interaction of feedback with achievement motivation does not have a simultaneous effect on the learning outcomes of understanding and application of concepts in teaching PPKn in SMK.